ANALISIS KESALAHAN BERBAHASA DALAM KARANGAN SISWA KELAS VI SEKOLAH DASAR - elvima nofrianni; Sundahry (Jurnal Tunas Pendidikan, 2026)
This study aims to describe the forms and frequency of language errors in sixth-grade elementary school students' compositions. The study used a qualitative descriptive approach by analyzing 20 student-composed texts using a reading-note-taking technique. The data were then classified based on error categories including spelling, word formation, sentence structure, and meaning. The results showed that spelling errors were the most dominant type of error, followed by errors in word formation, sentence structure, and meaning. These findings indicate that students' mastery of Indonesian language rules is still suboptimal, especially in terms of writing accuracy and word choice. The discussion of the study emphasizes the need for more targeted writing learning strategies, intensive practice, and continuous feedback from teachers. In addition to providing a picture of students' language error patterns, this study also opens up opportunities for further development, such as implementing learning interventions or developing special training media that can improve students' language accuracy.